Rail infrastructure costing based on multi-level full cost allocation - Bokor, Zoltán (Periodica Polytechnica Transportation Engineering, 2012)
Due to charging issues costs of rail infrastructure use shall be determined as exactly as possible. At the same time rail infrastructure management is a very complex system characterised by a high ratio of indirect costs. There are several costing methods used in transport and logistics but none of them gives a transparent and traceable solution for allocating indirect costs. That is why the paper aims to elaborate a transport cost calculation model adopting and utilising the multi-level full cost allocation method. The developed model and the calculation process are specified for rail infrastructure management. The new cost calculation system delivers more reliable and accurate cost data of elementary rail infrastructure services by allocating indirect costs on a cause-effect basis. At the same time additional resources may be needed for the implementation of the model. Nevertheless, as rail infrastructure manager companies request more exact cost data they should consider the implementation of the proposed costing model.